The problem of intentionality in analytic philosophy - Negru, Teodor (Видавництво Львівської політехніки, 2011)
In this paper I intend to show how the idea of intentionality has been discussed in analytic tradition of philosophy. In philosophy of language, intentionality has been understood as being related with the problem of referentiality. In this context, referentiality was approached as a theory of the meaning where the issue is the relationship between the meaning of an expression, its linguistic form, and the referent such phrase expression refers to. However, philosophy of mind give intentionality a naturalistic account, trying to explain it form the point of view of science. But al this attempts to naturalize intentionality stressed the difficulties of understanding this phenomenon from the point of view of natural science.
Проблема інтенціональності в аналітичній філософії
Keywords: intentionality; analytic philosophy; philosophy of mind; philosophy of language; naturalisation